Implementasi pendekatan inkuiri dalam pembelajaran biologi untuk meningkatkan kualitas belajar siswa SMP - Wulandari, Ayu; Apsari, Lisa; Febrian, Muhammad Rifqy; Maulida, Rahmah; Zaini, Muhammad; Putra, Aminuddin Prahatama; Fajeriadi, Hery; Belawati, Octa; Otari, Widiati Hairina (Journal of Bio-Creaducation, 2025)
This study aims to enhance the learning quality of junior high school students through the implementation of a guided inquiry learning model using image media in science education. The research method employed is Classroom Action Research (CAR), consisting of two cycles, with each cycle encompassing the stages of planning, implementation, observation, and reflection. The subjects of the study were 36 eighth-grade students in the odd semester of the 2022/2023 academic year. Data were collected through pretests, posttests, and observations of student activities during the learning process. The results indicate a significant improvement in student learning outcomes between the first and second cycles. This improvement was evident in both the cognitive and psychomotor domains, with the percentage of cognitive learning outcomes rising from 86.1% in the first cycle to 88.8% in the second cycle, and the percentage of student activity also showing consistent growth. Based on these results, it can be concluded that the guided inquiry learning model is effective in improving students' learning quality, particularly in science subjects. It is recommended that this approach be implemented more widely for other topics in biology education and supported by various media. Penelitian ini bertujuan untuk meningkatkan kualitas belajar siswa SMP melalui penerapan model pembelajaran inkuiri terbimbing dengan bantuan media gambar dalam pembelajaran IPA. Metode penelitian yang digunakan adalah penelitian tindakan kelas (PTK) yang terdiri dari dua siklus, dengan masing-masing siklus mencakup tahapan perencanaan, pelaksanaan, observasi, dan refleksi. Subjek penelitian adalah 36 siswa kelas VIII pada semester ganjil tahun ajaran 2022/2023. Data dikumpulkan melalui pretest, posttest, dan observasi aktivitas siswa selama proses pembelajaran. Hasil penelitian menunjukkan adanya peningkatan yang signifikan pada hasil belajar siswa antara siklus I dan II. Peningkatan terlihat pada ranah kognitif dan psikomotorik siswa, yang mana persentase hasil belajar kognitif meningkat dari 86,1% pada siklus I menjadi 88,8% pada siklus II, dan persentase keaktifan siswa juga mengalami peningkatan yang konsisten. Berdasarkan hasil ini, dapat disimpulkan bahwa model pembelajaran inkuiri terbimbing efektif dalam meningkatkan kualitas belajar siswa, khususnya pada mata pelajaran IPA. Disarankan agar pendekatan ini diimplementasikan lebih luas untuk topik-topik lain di pembelajaran biologi dan didukung oleh media yang bervariasi.